2014
DOI: 10.1007/s12031-014-0279-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic Responses of Neural Stem Cells to SDF-1α Correlate Closely with Their Differentiation Status

Abstract: Chemotaxis of neural stem/progenitor cells (NSCs) is regulated by a variety of factors, and much effort has been devoted to the delineation of factors that are involved in NSC migration. However, the relationship between NSC chemotactic migration and differentiation remains uncharacterized. In the present study, by comparing the transfilter migration rate, single-cell migration speed, and directional efficiency of NSCs in stromal cell-derived factor-1 alpha (SDF-1α)-induced Boyden chamber and Dunn chamber chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 80 publications
4
16
0
Order By: Relevance
“…There is evidence showing that some growth factors at high concentrations inhibit cell migration (Liang et al 2005). Consistently, our previous data demonstrate that the migratory response of neural stem cells to SDF-1a showed a typical biphasic dose-response curve (Chen et al 2014). All these findings indicate that MSCs at varying levels of Many studies have shown that PI3K/Akt and MAPK signaling pathways mediate cell migration induced by chemokines or cytokines (Bullone et al 2013;Yang et al 2013;Segarra et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…There is evidence showing that some growth factors at high concentrations inhibit cell migration (Liang et al 2005). Consistently, our previous data demonstrate that the migratory response of neural stem cells to SDF-1a showed a typical biphasic dose-response curve (Chen et al 2014). All these findings indicate that MSCs at varying levels of Many studies have shown that PI3K/Akt and MAPK signaling pathways mediate cell migration induced by chemokines or cytokines (Bullone et al 2013;Yang et al 2013;Segarra et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have identified that PI3K is involved in multiple stem cell migration40. The same phenomenon has also been demonstrated in leukemic cell lines55 and neural precursor cells56. The increased MSC migration by SDF-1 and hypoxia were both mediated by PI3K/Akt pathway57, which could be significantly attenuated by PI3K inhibitor.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have confirmed the variable nature of the effects elicited by SDF-1 and the dependency of associated effects on the differentiation status of the responding cell (Chen et al, 2014;Kokovay et al, 2010); however, the molecular mechanisms that underpin these reactions are unclear. To explore the expression patterns associated with CXCR4 in SVZ in vivo, we performed immunohistochemical analyses on SVZ whole mounts and observed that the immune stain signal was weaker from DCX-positive neuroblasts than from GFAP-positive astrocytes or type B NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Adult SVZ lineage cells have been observed to locate to, and subsequently leave, vascular niches because of differential responses to SDF1/CXCR4 signaling (Kokovay et al, 2010). More recent studies by Chen revealed that SDF-1α elicits different chemotactic effects on NPCs depending on their differentiation status (Chen et al, 2014). These findings indicate that SDF-1 affects each subpopulation of NPCs differently and the molecular mechanisms underpinning these events remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%